The Effect of Environment-Based Experiential Learning on Students’ Science Literacy and Ecological Awareness - Fatmawati Fatmawati; Yunus Abidin; Anita Yus; Yusrizal Yusrizal; Fira Astika Wanhar (MASI Mandiri Edukasi, 2026)
Science literacy and ecological awareness are essential competencies in 21st-century education; however, elementary learning often emphasizes conceptual understanding rather than real-life application, resulting in low student engagement and limited environmental awareness. Previous studies have examined experiential learning or inquiry approaches separately, but comparative studies integrating both cognitive and affective outcomes remain limited. This study aims to analyze and compare the effects of an experiential learning approach grounded in the environment and an inquiry approach on students’ science literacy and ecological awareness. This research employed a quantitative posttest-only design involving two experimental groups with a total of 144 elementary students. Data were collected using a science literacy test adapted from the PISA framework, an ecological awareness questionnaire, and a student response questionnaire. Data were analyzed using multiple linear regression. The results show that the experiential learning approach has a significant positive effect on both science literacy and ecological awareness and is more effective than the inquiry approach. In contrast, student responses do not significantly influence learning outcomes. These findings highlight the importance of direct and contextual learning experiences in improving both cognitive and environmental competencies. This study contributes to the development of experiential learning in elementary education and provides practical implications for designing more meaningful and sustainability-oriented learning.